The Influence of Service Level and Relational Promotion on the Decision to Stay at Hotel Platinum Rantauprapat - Muhammad Zunnil Akhyari; Basyarul Ulya; Endi Zunaedy Pasaribu (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the significant or not influence of the level of service and relational promotion on the decision to stay at the Platinum Rantauprapat hotel. The study used quantitative methods and through an associative causality approach. The data collection technique used was through observation and interviews. The sample in this study was 50 respondents or consumers. The sampling technique was simple random sampling. The data analysis technique used statistical techniques/SPSS by conducting validity and reliability tests then for questionnaires and multiple linear regression analysis with the T Test and F Test to prove the hypothesis. The results of the study showed that there was a close and significant influence of the level of service on the decision to stay, there was a close and significant influence of relational promotion on the decision to stay, the influence of friendliness to customers and the availability of goods was 98.6% and the remaining 1.4% was influenced by other factors and variables